Digital and Media Literacies in the Polish Education System-Pre- and Post-COVID-19 Perspective - Karina Cicha; Paulina Rutecka; Mariia Rizun; Artur Strzelecki (MDPI AG, 2021)
Digital and media literacies refer to a specific set of skills and abilities. The range of these skills as they concern the educational process has been broadly discussed. In this paper, we analyzed the Polish educational system to determine the scope of the sorts of digital skills young people and students should achieve in order to be considered digitally and media literate. We compared sets of recommendations from the last ten years issued by different national governmental and nonprofit organizations for the Polish education system. We identified a set of skills that should be expected to be possessed by young people and students during their education. Additionally, we discussed results regarding the situation caused by the COVID-19 pandemic and the shift from regular education to distance learning.